2000
DOI: 10.1007/s004170000196
|View full text |Cite
|
Sign up to set email alerts
|

Scanning laser polarimetry, retinal nerve fiber layer photography, and perimetry in the diagnosis of glaucomatous nerve fiber defects

Abstract: NFP and SLP mostly showed good agreement or little deviation as to grading of nerve fiber layer damage. In clinical use, SLP has advantages over NFP because a higher rate of good-quality images can be obtained and pupils do not have to be dilated. Additionally, SLP measurements provide quantitative data and a large normative data base exists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…10 If a decrease in the RNFL can be reliably detected, the clinician may be alerted to the risk for developing glaucoma. 8,9 To the best of our knowledge, there have not been any reports evaluating RNFL thickness in patients with OSAS, even though an association between glaucoma and sleep apnoea syndrome has been reported. [3][4][5][6] In this study, we measured the RNFL thickness to assess retinal nerve fibre injury reflected by thinning of this layer in OSAS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 If a decrease in the RNFL can be reliably detected, the clinician may be alerted to the risk for developing glaucoma. 8,9 To the best of our knowledge, there have not been any reports evaluating RNFL thickness in patients with OSAS, even though an association between glaucoma and sleep apnoea syndrome has been reported. [3][4][5][6] In this study, we measured the RNFL thickness to assess retinal nerve fibre injury reflected by thinning of this layer in OSAS.…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by characteristic visual field defects. 9 Patients with glaucoma can lose 40% of retinal ganglion cell axons before a measurable visual defect is evident. 10 Early detection of RNFL thinning offers an opportunity to detect glaucoma at its earlier stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kremmer and colleagues 167 found that 4.7% of their population could not undergo SLP. However, the authors did not state the characteristics of their population with regard to acuity, refractive error and visual field status.…”
Section: Discussionmentioning
confidence: 98%
“…This thinning can be present in the eyes of the patients with glaucoma before detectable changes occur in the visual field. 22,23 If a decrease in the RNFLT can be reliably detected, the clinician may be alerted for the risk of developing glaucoma. To the best of our knowledge, there is only one report evaluating RNFLT in patients with OSAS.…”
mentioning
confidence: 99%